Опорный каркас устойчивого развития региона (теоретический аспект) - Шарыгин, Михаил Дмитриевич; Назаров, Николай Николаевич; Субботина, Татьяна Васильевна (Географический вестник=Geographical bulletin, 2017)
нет аннотации